Modern system of psychoprophylaxis of autoagressive behavior in patients with bipolar affective disorder - Kozhyna, Hanna; Takhtashova, Dina; Koltsova, Galina (ScienceRise: Medical Science, 2018)
The aim. To develop a pathogenetically justified system of psycho prophylaxis of auto-aggressive behavior in BAD patients on the basis of studying the features and formation. Material and methods of the research. To solve the goal, following the principles of bioethics and deontology, a comprehensive clinical, psychopathological and psycho-diagnostic examination of 117 patients with BAD with signs of auto-destructive behavior, of both sexes, at an average age of 40.5 ± 5.5 years was carried out. Research methods: clinical, psychopathological, psycho-diagnostic, statistical. Results. In the course of the work, it was found that 48.7 ± 2.4% of the surveyed registered an affective version of auto-aggressive behavior, 31.5 ± 1.9% - true, 19.8 ± 1.1% - a demonstrative version and described their features depending on the polarity of the affect. Auto-aggressive behavior in the manic episode of BAR was associated with the prevalence of irritable mania in combination with a high level of frustration in the sphere of active life and independence of actions, a high level of internality in the field of achievements and low failures in the industry. With a depressive episode of BAR - the prevalence of dreary depression, combined with a high level of frustration in the field of love and family relationships, a high level of internality in the field of family relationships and failures. With a mixed episode of BAR - a combination of irritable mania and anxious depression in combination with a pronounced degree of frustration in the material and domestic sphere, a high level of internality in the area of failures and a low level of internality in the field of performance. A pathogenetically substantiated system for the prevention of auto-aggressive behavior in patients with BAR has been developed, which consists of five stages: crisis therapy, a comprehensive diagnosis, basic and supportive therapeutic and preventive measures, and socio-psychological assistance. And it includes the use of methods of pharmacotherapy, psychotherapy and psychosocial therapy. Conclusions. Based on the obtained data in the course of the work, a pathogenetically substantiated system for the prevention of suicidal behavior of BAR patients has been developed, which consists of five stages: crisis therapy, a comprehensive diagnosis, main and supportive treatment and preventive measures, and socio-psychological assistance. The means of therapeutic influence at all stages were applied in the form of pharmacotherapy, psychotherapy and psychosocial care